Program pembelajaran bagi siswa dengan ADHD di SDN Rejowinangun Yogyakarta - Novami, Fera; Prakoso, Bima (Literal: Disability Studies Journal, 2023)
This study aims to obtain an overview of the learning program for students with ADHD  at Rejowinangun Elementary School in the 2020/2021 academic year. This descriptive qualitative research had subjects consisted of a class teacher and a student who had been diagnosed with ADHD. Data was collected through interviews and observation. The data validity was conducted by increasing persistence, triangulation, and using reference materials. Data analysis techniques was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study illustrate that it needs to carry out further studies regarding efforts to overcome various problems of teacher capacity in designing appropriate learning for students in inclusive schools, dealing with behavioral problems, and establishing cooperation with parents/guardians as a support system for children's success. Further research is still needed with more subjects and locations by other researchers in order to get a more in-depth study of learning practices for students with ADHD in inclusive schools.